The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/2015ja021393
|View full text |Cite
|
Sign up to set email alerts
|

Formation of polar ionospheric tongue of ionization during minor geomagnetic disturbed conditions

Abstract: Previous investigations of ionospheric storm‐enhanced density (SED) and tongue of ionization (TOI) focused mostly on the behavior of TOI during intense geomagnetic storms. Little attention has been paid to the spatial and temporal variations of TOI during weak to moderate geomagnetic disturbed conditions. In this paper we investigate the source and development of TOI during a moderate geomagnetic storm on 14 October 2012. Multi‐instrumental observations including GPS total electron content (TEC), Defense Meteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 44 publications
2
33
0
Order By: Relevance
“…Near the geomagnetic poles, the vertical plasma transport due to the horizontal thermospheric wind is zeroed. Our results are in agreement with previous findings by Liu et al (), Liu, Wang, Burns, Solomon, et al (). These authors have demonstrated that the TOI is enhanced due to equatorward upwelling of plasma at the dayside subauroral latitudes in the region of plasma accumulation before its removal to the polar cap.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Near the geomagnetic poles, the vertical plasma transport due to the horizontal thermospheric wind is zeroed. Our results are in agreement with previous findings by Liu et al (), Liu, Wang, Burns, Solomon, et al (). These authors have demonstrated that the TOI is enhanced due to equatorward upwelling of plasma at the dayside subauroral latitudes in the region of plasma accumulation before its removal to the polar cap.…”
Section: Resultssupporting
confidence: 94%
“…Sojka et al () reported that under conditions of enhanced magnetospheric convection, TOI is more pronounced. The main characteristics of the TOI occurrence during strong geomagnetic storms have been studied using multi‐instrumental observations and theoretical models (e.g., Foster et al, ; David et al, ; Liu et al, , Liu, Wang, Burns, Solomon, et al, ; Liu, Wang, Burns, Yue, et al, ; Thomas et al, ). Often, occurrence of TOI is linked to another storm time plasma feature—SED, a localized plume‐like increase of ionospheric electron density (particularly the total electron content [TEC]), which is transported poleward from a source region at middle latitudes (Coster & Scone, ; Foster, ).…”
Section: Introductionmentioning
confidence: 99%
“…Resultant antisunward convection in the middle of the polar cap can lead to (segmented or unsegmented) TOI [e.g., Zhang et al , ; Walsh et al , ], which is elongated across different L shells by definition. Note that TOIs can occur during strong as well as moderate to weak geomagnetic storms [e.g., Liu et al , , and references therein]. As our study imposes no constraints on geomagnetic activity, TOIs will also contribute to the statistics in the polar cap, as shown in Figures and .…”
Section: Discussionmentioning
confidence: 77%
“…Storm time, single‐site observations from the Millstone Hill Incoherent Radar (ISR) frequently show dramatic F region electron density enhancements around the duskside, which is termed the “dusk effect” [e.g., Papagiannis et al ., ; Mendillo et al ., ; Evans , ; Anderson , ; Buonsanto , , , ]. Based on Millstone Hill ISR 2‐D electron density measurements, Foster [] renamed this phenomenon SED, which is typically characterized by a latitudinally distinct region of sunward convection F region plasma, high electron densities, an elevated F region peak, a significantly enhanced topside ionosphere, and low electron temperatures near sunset at middle latitudes [ Foster , ; Liu et al ., , ]. Cherniak and Zakharenkova [] reported that high‐latitude ionospheric irregularities tend to occur in the edge of SED/TOI having steep ionospheric density gradients during the St. Patrick's Day event in 2015.…”
Section: Introductionmentioning
confidence: 99%
“…In some literatures, people do not distinguish between SED and TOI since these two are quite similar but occur at different latitudes. However, Liu et al [2015] reported that TOI can also occur during geomagnetic quiet or weakly disturbed conditions at favorable universal local times independent of SED occurrence. TOI tends to form during the universal times when high-latitude two-cell convection patterns are closer to solar-produced middle-latitude plasma source region, facilitating the poleward plasma transportations.…”
Section: Introductionmentioning
confidence: 99%